Specific Intermolecular Interactions by the Localized π‐Electrons in C70‐fullerene. Issue 18 (14th November 2016) - Kubo, Takuya; Kanao, Eisuke; Matsumoto, Takatoshi; Naito, Toyohiro; Sano, Tomoharu; Yan, Mingdi; Otsuka, Koji
Abstract: We report the specific intermolecular interactions on C70 ‐fullerene. A newly developed silica‐monolithic capillary column, which was modified with C70 ‐fullerene via a particular thermal reactive molecule, perfluorophenyl azide, provided a selective retention behavior toward polycyclic aromatic hydrocarbons in liquid chromatography. Especially, a hemispherical molecule, i. e., corannulene, was significantly retained on this C70 ‐fullerene column. Results of the computer simulation of the molecules suggested that the specific interaction might be caused by the deflection of the π‐electrons‐density in C70 ‐fullerene. Furthermore, the absorption spectrometry also indicated that the absorption spectra of C70 ‐fullerene with/without corannulene were dramatically changed by the specific interaction, whereas no spectrum differences were observed with C60 ‐fullerene. Abstract : C70 ‐fullerene (C70) bonded silica monolith was successfully prepared. The monolith showed a strong interaction based on the π‐stacking in liquid chromatography. Also, a hemispherical molecule, corannulene (Crn), was specially interacted with C70. The result of the computer simulation and the change in the absorption spectra associated with the interaction between C70 and Crn suggested that the significant induced‐dipole interaction was worked in C70.